Metabolic profile and skin-related bioactivities of Cerioporus squamosus hydromethanolic extract - Waill Elkhateeb; Ghoson Daba; Marwa Elnahas; Paul Thomas; Mahmoud Emam (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Elkhateeb WA, Daba GM, Elnahas MO, Thomas PW, Emam M. 2020. Metabolic profile and skin-related bioactivities of Cerioporus squamosus hydromethanolic extract. Biodiversitas 21: 4732-4740.  Being a functional food capable of showing nutritional as well as medicinal properties have great attention. Mushrooms have been proven as leading targets in this field. For this purpose, the edible mushroom Cerioporus squamosus was investigated in this study to evaluate the in vitro skin-related bioactivities of its hydromethanolic extract in terms of enhancing wound healing, and human skin cancer suppression capabilities. Treatment of fibroblast cells (BJ-1) with the hydromethanolic extract of this mushroom at 50 µg/mL enhanced cell migration rates by 71.7% after 24 h of exposure to the extract. Moreover, the same extract exhibited a promising impact on human skin cancer using an epidermoid carcinoma cell line (A431). The gradual increase in C. squamosus hydromethanolic extract concentration caused gradual decrease in the A431 cell viability and proliferation. Maximum effect on reducing the cell viability was obtained at a concentration of 100 µg/mL, where cell viability was 3.7%, and recorded IC50 was 52.6 µg/mL. The metabolic profile of the extract was analyzed by GC-MS, which was performed on its silylated metabolites. Nineteen compounds were detected including sugar alcohols, amino acids, fatty and organic acids. Promising results of this mushroom extract encourage conducting further steps towards using this mushroom as a functional food showing promising bioactivities.